Global convergence of RTLSQEP: A solver of regularized total least squares problems via quadratic eigenproblems - Lampe, Jörg; Voss, Heinrich (Mathematical Modelling and Analysis, 2008)
The total least squares (TLS) method is a successful approach for linear problems if both the matrix and the right hand side are contaminated by some noise. In a recent paper Sima, Van Huffel and Golub suggested an iterative method for solving regularized TLS problems, where in each iteration step a quadratic eigenproblem has to be solved. In this paper we prove its global convergence, and we present an efficient implementation using an iterative projection method with thick updates.First Published Online: 14 Oct 2010